2021
DOI: 10.1016/j.polymer.2021.123734
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interlayer adhesion and warping during material extrusion-based additive manufacturing of a carbon nanotube/biobased thermoplastic polyurethane nanocomposite

Abstract: A thermoplastic bio-polyurethane from renewable sources (TPU) and the nanocomposite developed by mixing it with carbon nanotubes (CNT) are investigated as potentially adequate for Material Extrusion-based Additive Manufacturing (EAM). Thermal and rheological features are studied from the perspective of their liaisons with printing adequacy and conditions. As predicted by rheology, both samples show good performance in filament elaboration and flow in the nozzle. Warpage is observed for TPU, but not for the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…According to the experimental design, CRFRPP with different printing parameter combinations were manufactured and their interfacial properties (interlayer and intralayer adhesion properties) were examined. Inspired by these works [32,[37][38][39][40][41][42][43] and ASTM D1938 investigated the tensile properties of ME-AM fabricated continuous flax fiber reinforced PLA composites. The results showed that the longitudinal tensile modulus and strength of continuous flax fiber reinforced PLA composites were improved by a factor of 4.5.…”
Section: Characterizationmentioning
confidence: 99%
“…According to the experimental design, CRFRPP with different printing parameter combinations were manufactured and their interfacial properties (interlayer and intralayer adhesion properties) were examined. Inspired by these works [32,[37][38][39][40][41][42][43] and ASTM D1938 investigated the tensile properties of ME-AM fabricated continuous flax fiber reinforced PLA composites. The results showed that the longitudinal tensile modulus and strength of continuous flax fiber reinforced PLA composites were improved by a factor of 4.5.…”
Section: Characterizationmentioning
confidence: 99%
“…The degree of chain orientation at the interlayer region as well as the morphological features of printed parts are strongly influenced by the processing parameters 28 . The adhesion energy (or tear energy) determined from the trouser tear tests for PLA prints serves as a measure of the interlayer weld strength 44,48,55,56 . Figure 5…”
Section: Please Cite This Article As Doi: 101063/50128660mentioning
confidence: 99%
“…For FFF, agglomeration of CNTs can lead to flux instability, blockage of the nozzles, and failure of the printing work. [128,147] Candal et al [148] studied the correlation between the rheological features and thermal behavior (using calorimetric and dilatometric experiments) of a bio-based TPU/4 wt% CNT nanocomposite and its performance during FFF. The results obtained showed that the viscous modulus (G 00 ) is greater than the elastic modulus (G 0 ) of the nanocomposites, except at frequencies close to 100 Hz, at which the rubbery zone starts and G 0 is greater than G 00 for both the neat and filled TPU.…”
Section: Carbon Nanotube Nanocompositesmentioning
confidence: 99%